Effectiveness of Distribution of Baitul Mal Humanist Action Program (BaGAH) Aceh - Wirdiyan, Adib; Abubakar, Ali; A.Jalil, Husni (Universitas Islam Negeri Ar-Raniry, 2025)
This Study Examines The Effectiveness Of The Distribution Of Urgent Financial Assistance For Victims Of Natural Disasters, Humanitarian Disasters, Companions Of Sick People Who Are Referred Out Of Town, Travelers Who Run Out Of Supplies, Or Other Assistance That Is Emergency And Urgent. This Study Is Considered Important Because Every Financial Assistance That Is Disbursed Must Precede The Aceh Revenue And Expenditure Budget (APBA) So That All Activities That Use Zakat Funds Cannot Be Distributed Before The ABPA Is Approved. This Hampers The Distribution Of Urgent Financial Assistance. To Explain This, Two Questions Are Asked: (1) What Is The Description Of The Baitul Mal Aceh Humanist Action Program? (2) What Is The Effectiveness Of The Distribution Of Baitul Mal Aceh Humanist Action Program? The Method Used In This Writing Is Through A Qualitative Study Process Sourced From The Results Of Interviews With Baitul Mal Staff And Data On The Distribution Of Funds That Have Been Distributed By The Baitul Mal Institution Through The Bagah Program Which Has Been Implemented Since The Beginning Of The Bagah Service. The Data Were Analyzed Using The Theory Of Effectiveness And Explained With The Concept Of Baitul Mal And Its Relationship To Zakat, Regulations Related To The Management Of The Aceh Government Budget And The Theory Of Effectiveness. The Results Of The Study Show That Bagah Has Three Classifications In The Distribution Of Funds. First, Isidentil Asnaf (Poor) Namely Sick People And People Who Accompany Sick People. Second, Asnaf (Gharim) Namely Victims Of Natural Disasters Such As Floods. Third, Displaced People Are Included In The Asnaf Ibnu Sabil Namely Migrants From Aceh.